ANALYSIS OF THE INFLUENCE OF eWOM ON IMPULSE BUYING DECISIONS WITH TRUST: A STUDY ON ONLINE FASHION SHOP - Mubalus, Matelda (SOSCIED, 2024)
Many studies have been conducted on electronic word of mouth (eWOM) and have shown varying results, therefore a more comprehensive review needs to be carried out. The aim of this study is to build a model of the relationship between eWOM variables (quality and quantity) on impulse buying which is mediated by trust. The analytical method used was an explanatory method by explaining the causal relationship between eWOM variables (quality and quantity), trust, and impulse buying. The population in this study were people who had shopped online with a sample of 340 people. The analytical tool used Structural Equation Modeling (SEM) with AMOS software tools. We found that eWOM (quality and quantity) influences impulse buying.